Crater shape as a possible record of the impact environment of metallic bodies: Effects of temperature, impact velocity and impactor density - Ogawa, Ryo; Nakamura, Akiko M.; Suzuki, Ayako I.; Hasegawa, Sunao (Icarus (New York, N.Y. 1962), 2021)
Metallic bodies that were the cores of differentiated bodies are sources of iron meteorites and are considered to have formed early in the terrestrial planet region before migrating to the main asteroid belt. Surface temperatures and mutual collision velocities differ between the terrestrial planet region and the main asteroid belt. To investigate the dependence of crater shape on temperature, velocity and impactor density, we conducted impact experiments on room- and low-temperature iron meteorite and iron alloy targets (carbon steel SS400 and iron‑nickel alloy) with velocities of 0.8–7 km s−1. The projectiles were rock cylinders and metal spheres and cylinders. Oblique impact experiments were also conducted using stainless steel projectiles and SS400 steel targets which produced more prominent radial patterns downrange at room temperature than at low temperature. Crater diameters and depths were measured and compiled using non-dimensional parameter sets based on the π-group crater scaling relations. Two-dimensional numerical simulations were conducted using iSALE-2D code with the Johnson–Cook strength model. Both experimental and numerical results showed that the crater depth and diameter decreased with decreasing temperature, which strengthened the target, and with decreasing impact velocity. The decreasing tendency was more prominent for depth than for diameter, i.e., the depth/diameter ratio was smaller for the low temperature and low velocity conditions. The depth/diameter ratios of craters formed by rock projectiles were shallower than those of craters formed by metallic projectiles. Our results imply that the frequency distribution of the depth/diameter ratio for craters on the surface of metallic bodies may be used as a probe of the past impact environment of metallic bodies. •Impact experiments on room- and low-temperature iron meteorite and iron alloy targets were conducted.•Oblique impact experiments produced more prominent radial patterns downrange at room temperature than at low temperature.•Crater depth/diameter ratio was smaller for the low temperature and low velocity conditions.•The depth/diameter ratio of craters on metallic surfaces contain information about the past impact environment.